Pembuatan Histogram Dan Pola Data Warna Urin Berdasarkan Urinalisis Menggunakan Mini PC - Andrizal Andrizal; Anton Hidayat; Tuti Angraini; Yefriadi Yefriadi; Rusfandi Rusfandi; Rivanol Chadry (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2018)
The method for observing urine color to diagnose a disease of patient has done so far. The visual observation with human eyes has done to study and analyze human urine color and detect the connected disease. Human vision lately can be replaced with computer visual system or other sensor or camera to detect that color. The color of object is composed by two color components, they are frequency and spatial domain. Therefore, each color has wavelength and form in number of frequency. Color censor TCS 3200 produces output signals with different frequency based on scanned color through photodiode of the censor. Recognizing of the object in the form of shape, color and other variables of the object. Feature extraction is obtain from the data pattern as well as histogram. This research aims generate histogram and urine color pattern according to patient situation indication. The use of color reference is main color urinalysis, the result of method at Cleveland in Ohio in 2013. Based on the research, the pattern and color histogram were obtained in different style found in detected different urine color. This research would contribute to help identification process of diseases based on urine color thorough online.